2008
DOI: 10.1093/bja/aen054
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anaemia management: consensus statement on the role of intravenous iron

Abstract: A multidisciplinary panel of physicians was convened by Network for Advancement of Transfusion Alternatives to review the evidence on the efficacy and safety of i.v. iron administration to increase haemoglobin levels and reduce blood transfusion in patients undergoing surgery, and to develop a consensus statement on perioperative use of i.v. iron as a transfusion alternative. After conducting a systematic literature search to identify the relevant studies, critical evaluation of the evidence was performed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
138
0
21

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 41 publications
2
138
0
21
Order By: Relevance
“…Depending on the type of surgery, underlying disease and the definitions of anaemia, about 11% to 76% of surgical patients may present with pre-operative anaemia [3,4]. Recently, there has been increasing evidence to suggest that pre-operative anaemia can lead to an increased risk of peri-operative adverse outcomes such as increased post operative infections, increase the requirement for blood transfusion, increase of hospital Length of Stay (LoS) and increased overall morbidity and mortality [5][6][7].…”
Section: Design Overviewmentioning
confidence: 99%
“…Depending on the type of surgery, underlying disease and the definitions of anaemia, about 11% to 76% of surgical patients may present with pre-operative anaemia [3,4]. Recently, there has been increasing evidence to suggest that pre-operative anaemia can lead to an increased risk of peri-operative adverse outcomes such as increased post operative infections, increase the requirement for blood transfusion, increase of hospital Length of Stay (LoS) and increased overall morbidity and mortality [5][6][7].…”
Section: Design Overviewmentioning
confidence: 99%
“…Patients may also have vitamin B12 or folate deficiencies [18,29]. A retrospective observational study evaluating the characteristics of pre-operative anaemia in patients undergoing elective orthopaedic joint arthroplasty found that 64% of patients had a normochromic normocytic anaemia, 23% a hypochromic anaemia and 12% had other types of anaemia [30]. Acute pre-operative anaemia is uncommon in clinically stable elective cases, but is frequently associated with significant haemorrhage as occurs in obstetrics and following trauma [20].…”
mentioning
confidence: 99%
“…Par exemple, jusqu'à 75 % des patients se présentant pour une chirurgie non urgente peuvent être atteints d'anémie en période préopératoire, et près de 90 % des patients pourraient souffrir d'anémie après la chirurgie. 5 Chez une grande proportion de ces patients, l'anémie s'explique par une carence en fer ou par une maladie chronique. [6][7][8][9][10][11] En période peropératoire, l'anémie chronique est un facteur de risque d'anémie aiguë, qui survient fréquemment en raison d'une combinaison de perte aiguë de sang et d'hémodilution provoquée par la réanimation liquidienne (he´modilution).…”
Section: Clinical Caseunclassified